2011
DOI: 10.1021/jz2001979
|View full text |Cite
|
Sign up to set email alerts
|

Emission Quenching in PbSe Quantum Dot Arrays by Short-Term Air Exposure

Abstract: Clear evidence for two emitting states in PbSe nanocrystals (NCs) has been observed. The flow of population between these two states as temperature increases is interrupted by the presence of nonradiative trap states correlated with the exposure of the NC film to air. Quenching of the higher-energy emission begins after only seconds of exposure, with the effect saturating after several days. Unlike short-term oxygen-related effects in solution, the emission quenching appears to be irreversible, signaling a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 27 publications
(47 reference statements)
4
76
0
Order By: Relevance
“…Nonmonotonic PL yield persists even after their samples are exposed to a controlled oxygen environment from minutes to hours. This behavior is attributed to PL contributions from two distinct radiative states at different energies in these QD samples, consistent with spectral lineshape analysis, at least in dilute glass-encased samples, No air exposure during QD synthesis or as drop cast; Chappell et al [10]. Same QD drop-cast sample as traces B 2 through B 5 .…”
Section: Summary Of Photoluminescence Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Nonmonotonic PL yield persists even after their samples are exposed to a controlled oxygen environment from minutes to hours. This behavior is attributed to PL contributions from two distinct radiative states at different energies in these QD samples, consistent with spectral lineshape analysis, at least in dilute glass-encased samples, No air exposure during QD synthesis or as drop cast; Chappell et al [10]. Same QD drop-cast sample as traces B 2 through B 5 .…”
Section: Summary Of Photoluminescence Resultssupporting
confidence: 81%
“…Same QD drop-cast sample as traces B 2 through B 5 . B 2 1 minute of air exposure as drop cast, none during QD synthesis; Chappell et al [10]. B 3 Thirty minutes of air as drop cast, none during QD synthesis; Chappell et al [10].…”
Section: Summary Of Photoluminescence Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We take this evidence as proof that the dual band is an intrinsic property of the electronic structure of the samples. 27,30 and exsperimentally 21,23,29,[31][32][33] . These studies have suggested that splitting within the exciton fine structure near the band gap may be responsible 23,27,29 .…”
mentioning
confidence: 99%